MEMITIGASI PENGARUH PERSONAL COST TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING PADA APARATUR SIPIL - Pasangka, Praja Habib (APSSAI, 2021)
Corruption Perception Index data shows that Indonesia is one of the countries prone to corruption though the trend is decreasing every year. There have been many efforts to minimize it, one of which is through the role of whistleblowers. However, whistleblowers are always faced with a dilemma between reporting fraud and protecting themselves from reporting fraud. It is necessary to have dilemma mitigation mechanism thus the intention to carry out whistleblowing can be realized into action and can prevent and reveal fraudulent practices. For this reason, the researcher tries to examine the role of reward to mitigate the effect of personal costs in creating the dilemma in question. Using a survey method, the results show that personal costs have a positive effect on the intention of whistleblowing, which causes the role of reward to be insignificant in mediating the effect of personal cost on the intention to do whistleblowing.